Characterization of chemical compound and cellulose content in kenaf core - Zakaria, Siti Raihan (2017)
Kenaf plant or its scientific name is Hibiscuss Cannabinus L. is one of the sources of cellulose that can be implemented with economic and ecological advantage. Nowadays, kenaf core is used to make paper, textile, adsorbent and polymer composite due of its special properties which is environmental friendly and good potential reinforcement material. This study is conducted to characterize the chemical compound and cellulose content in core kenaf as well as investigating the effect of five bleaching process on the characteristics of kenaf core fiber. Alkali treatment and bleaching process are conducted to prepare cellulose. In this study, alkali treatment is conducted by using 4wt% sodium hydroxide followed by bleaching using 1.7 wt% sodium chloride in acetate buffer. The characterization of kenaf core, alkaline-treated kenaf core, 1 st bleached kenaf core, 3rd bleached kenaf core and 5th bleached kenaf core are analysed by using Fourier transform infrared spectroscopy(FTIR), X-ray diffractometer (XRD) and Thermalgravimetric analysis(TGA). FTIR results showed the removal of non-cellulosic materials for each subsequent treatment. It also showed that the 5th bleached kenaf core has the highest degree of crystallinity which is 76.4% while raw kenaf core show the lowest which is 55.8%. Thermal analysis results showed that the content of cellulose is increased after the chemical treatment.